Kompetensi Lulusan Perguruan Tinggi Vokasi Dalam Strategi Mewujudkan Sumberdaya Yang Berwawasan Entrepreneur - Enny Diah Astuti (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This study analyzes the competencies of vocational college graduates with entrepreneurial-minded resources. The problems examined in this study is about the discussion in realizing the competence of vocational college graduates in the strategy of realizing entrepreneurial-minded resources. This research is an empirical study of student graduates in vocational colleges. The selected population of the vocational college graduates are using 20 indicators out of 135 respondents from some of the high vocational college graduates in Bekasi that most of them are from Politeknik LP3I that is spreaded out in different campuses. The data collection will use questionnaires while the analysis tool was used for Structural Equation Modeling (SEM). The results of data analysis shows that this research model is acceptable with goodness of fit. The public synopsis from the test results model that was applied to the competence of high vocational college graduates shows that strategy implementation can manifest the entreprenuer-minded resources. This study also has some limits on the research agenda for the next study.